Dielectric relaxation in NaNbO₃ single crystal - Konieczny, K. (Condensed Matter Physics, 1999)
Dielectric permittivity studies of reduced samples of NaNbO₃ single crystal in the range of temperatures 30–500 °C and frequency 20 Hz-1 MHz are reported. In this temperature range a relaxation process is observed in the frequency range of about 100 kHz. This is an additional process to the earlier reported one [7]. The obtained data were ﬁtted to Cole-Cole formula. The dispersion step ∆ǫ (the maximum value of ∆ǫ =1000) is temperature dependent. The mean relaxation time τ does not obey the Arrhenius law above TC. The occurrence of this relaxation process may be connected with oxygen vacancies.